Using Running Dictation Game To Improve Grade Ten Students' Understanding On Simple Present Tense In SMA Negeri 2 Pematang Siantar - Fretty Riana Rajagukguk; David Togi Hutahean; Irene Adryani Nababan (Jurnal Ilmu Pendidikan dan Sosial, 2024)
This objective of this research is to find out the effect of using Running Dictation Game on Simple Present Tense SMA Negeri 2 Pematang Siantar in the academic year 2022/2023. Through the uses of a quasi-experimental design, this research uses a quantitative method. It has two classes, such as experimental class and control class which use in the research. 353 students in grade ten at SMA Negeri 2 Pematang Siantar make up the population of this research. Students from classes X-2 (experimental class) and X-1 (control class), who choose using the purposive sampling technique and make up the sample for this research. There are 10 multiple-choice questions and 10 essay on the research instrument, including a pre- and post-test that the researcher uses to assess the data. The researcher uses the t-test formula to assess the data. The result of this data shows that the mean score of pre-test in experimental class score is 74.5, while the mean post-test score is 92.7. In the control class, the pre-test mean is 63.2, and the post-test mean is 79.4. After calculating the mean score for both groups and using the t-test formula, the results show that the t-test has the highest significance level in the t-table with 5% level significance (1.807> 1,667). So, using running dictation game to improve grade ten has significant effect to the students’.